2012
DOI: 10.1002/art.34331
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of rituximab for the treatment of severe cryoglobulinemic vasculitis

Abstract: Objective. To conduct a long-term, prospective, randomized controlled trial evaluating rituximab (RTX) therapy for severe mixed cryoglobulinemia or cryoglobulinemic vasculitis (CV).Methods. Fifty-nine patients with CV and related skin ulcers, active glomerulonephritis, or refractory peripheral neuropathy were enrolled. In CV patients who also had hepatitis C virus (HCV) infection, treatment of the HCV infection with antiviral agents had previously failed or was not indicated. Patients were randomized to the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
218
1
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(242 citation statements)
references
References 39 publications
7
218
1
16
Order By: Relevance
“…This trial compared RTX (without or with low-dose steroids) to a conventional immunosuppressive treatment including corticosteroids, cyclophosphamide, azathioprine, or plasma exchange. This trial documented the superiority of RTX over standard therapy [54]. Duration of response to RTX of MC manifestations is difficult to define due to the lack of long-term follow-up data in most studies.…”
Section: Mixed Cryoglobulinemia-associated Glomerulonephritismentioning
confidence: 93%
“…This trial compared RTX (without or with low-dose steroids) to a conventional immunosuppressive treatment including corticosteroids, cyclophosphamide, azathioprine, or plasma exchange. This trial documented the superiority of RTX over standard therapy [54]. Duration of response to RTX of MC manifestations is difficult to define due to the lack of long-term follow-up data in most studies.…”
Section: Mixed Cryoglobulinemia-associated Glomerulonephritismentioning
confidence: 93%
“…69 Two randomized controlled trials published recently, have shown the efficacy of rituximab as compared to conventional therapy. 70,71 Role of expansion of T regulatory (Treg) cells with subcutaneous IL 2 injections and associated clinical improvement in patients with refractory HCV associated CV may suggest that low dose IL2 may promote tolerance but we will have to wait for further studies. 72 In future, other anti B cell targeted therapies like ocrelizumab and ofatumumab (anti CD20), epratuzumab (anti CD22) and belimumab (anti BAFF) might also prove useful in management of severe systemic/refractory manifestations.…”
Section: Management Of Mixed Cryoglobulinemiamentioning
confidence: 99%
“…It is possible that factors such as cytokines, growth factors and host genetic background may also link chronic HCV infection and lymphoproliferation [8,9].…”
Section: Introductionmentioning
confidence: 99%